Entitled women - but not men - make tougher strategic demands as proposers in the ultimatum game - Elif E. Demiral; Johanna Mollerstrom (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In a laboratory experiment subjects are matched in pairs and interact in an Ultimatum Game. In the Entitlement treatment, the right to be the proposer is allocated to the personin the pair who performed better in a previously conducted math task. Compared to behavior in the control treatment, where the roles are randomly allocated, the proposers increase their strategic demands and offer a smaller share of the pie to the responder in the Entitlement treatment. This result is drivenentirely by female proposers; when earning their role, they significantly lower their offers, whereas male proposers do not behave differently than when roles are randomly allocated. This is in line with previous research suggesting that women are more sensitive to contextual factors and social cues, meaning that strengthening feelings of entitlement could be a way to decrease gender differences innegotiation behavior.
Additional information: Newer version published at DP 1756 (2018). Please cite the new version: http://hdl.handle.net/10419/182227; More recent version: http://hdl.handle.net/10419/182227
Keywords: 330